State and problems of modernization of regional fiscal policy in the Republic of Kazakhstan - Lee Akyzhanov, V. S. D. M. (Journal of Economic Research & Business Administration, 2016)
The article covers the problems and the current state of regional and fiscal policy in the Republic of Kazakhstan, also the extracts from message of the President of the Republic of Kazakhstan, the review of economic sectors, analyses of deficits and methods of how to settle the problem of integration of the regional policy in our young state. The article also deals with the problems of everyday nature: inefficient spending of the state budget, outdated reforms related to regional policy. The article covers methods of a balanced budget in which revenues from the petroleum sector is completely sent to the national Fund, the National Fund sources, what type of monitoring will be developed and seamlessly integrated in order to consider in detail the expenditures of the Republican budget for current budget program. The system of indicators of estimation of efficiency of budget expenses and determination of its indicators, the introduction of which will allow you to track the level of efficiency of use of budgetary funds is also presented here.